2010
DOI: 10.1002/chin.201012105
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Cyclocondensation of α‐Aminonitriles and Enones: A Short Access to 3,4‐Dihydro‐2H‐pyrrole 2‐Carbonitriles and 2,3,5‐Trisubstituted Pyrroles.

Abstract: Cyclocondensation of α-Aminonitriles and Enones: A Short Access to 3,4-Dihydro-2H-pyrrole 2-Carbonitriles and 2,3,5-Trisubstituted Pyrroles. -Treatment of enones with aminoacetonitrile and aminonitriles derived from aromatic aldehydes provides a facile approach to dihydropyrroles like (III), (IV), and (XII). The latter can smoothly be transformed into trisubstituted pyrroles and pyrrolizidines. The reaction of α-aminonitriles generated form aliphatic aldehydes leads to imines of type (IX). Their treatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Opatz et al reported the base-catalyzed conjugate addition of 1-pyrroline-5-carbonitrile to α-enones in which adducts were converted to bicyclic pyrolidizine heterocycles. 7 Inspired by Opatz's work, we had previously studied the silver-catalyzed conjugate addition of 1pyrroline-5-carboxylate to α-enones followed by intramolecular reductive amination, which led to the stereoselective synthesis of pyrrolizidine carboxylate. 8 However, we did not study the reaction of 1-pyrroline-5-carbonitrile with α-enones at that time because of the difficulty in achieving stereocontrol of the imino nitrile.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Opatz et al reported the base-catalyzed conjugate addition of 1-pyrroline-5-carbonitrile to α-enones in which adducts were converted to bicyclic pyrolidizine heterocycles. 7 Inspired by Opatz's work, we had previously studied the silver-catalyzed conjugate addition of 1pyrroline-5-carboxylate to α-enones followed by intramolecular reductive amination, which led to the stereoselective synthesis of pyrrolizidine carboxylate. 8 However, we did not study the reaction of 1-pyrroline-5-carbonitrile with α-enones at that time because of the difficulty in achieving stereocontrol of the imino nitrile.…”
Section: ■ Introductionmentioning
confidence: 99%